How do you factor the expression # 6x^2 - 23x + 15#?

Answer 1

#6x^2-23x+15=(6x-5)(x-3)#

Use an AC method:

Find a pair of factors of #AC=6*15=90# with sum #B=23#
The pair #18, 5# works in that #18xx5 = 90# and #18+5=23#.

Use this pair to split the middle term and factor by grouping:

#6x^2-23x+15#
#=6x^2-18x-5x+15#
#=(6x^2-18x)-(5x-15)#
#=6x(x-3)-5(x-3)#
#=(6x-5)(x-3)#
#color(white)()# Alternatively, you can complete the square and use the difference of squares identity:
#a^2-b^2=(a-b)(a+b)#
with #a=(12x-23)# and #b=13# as follows:
I will multiply by #4*6 = 24# first to avoid some fractions:
#24(6x^2-23x+15)#
#=144x^2-552x+360#
#=(12x)^2-2(12x)(23)+360#
#=(12x-23)^2-23^2+360#
#=(12x-23)^2-529+360#
#=(12x-23)^2-169#
#=(12x-23)^2-13^2#
#=((12x-23)-13)((12x-23)+13)#
#=(12x-36)(12x-10)#
#=(12(x-3))(2(6x-5))#
#=24(x-3)(6x-5)#
Dividing both ends by #24# we find:
#6x^2-23x+15 = (x-3)(6x-5)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To factor the expression (6x^2 - 23x + 15), you can use the quadratic formula or factoring by grouping. In this case, factoring by grouping is simpler. First, find two numbers that multiply to (6 \times 15 = 90) and add to (-23). These numbers are (-5) and (-18). Rewrite the middle term using these numbers: (6x^2 - 18x - 5x + 15). Now, factor by grouping: (3x(2x - 6) - 5(2x - 6)). Factor out the common binomial (2x - 6): ((3x - 5)(2x - 6)).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7